2017
DOI: 10.3389/fonc.2017.00246
|View full text |Cite
|
Sign up to set email alerts
|

Fractal and Gray Level Cooccurrence Matrix Computational Analysis of Primary Osteosarcoma Magnetic Resonance Images Predicts the Chemotherapy Response

Abstract: The prediction of induction chemotherapy response at the time of diagnosis may improve outcomes in osteosarcoma by allowing for personalized tailoring of therapy. The aim of this study was thus to investigate the predictive potential of the so far unexploited computational analysis of osteosarcoma magnetic resonance (MR) images. Fractal and gray level cooccurrence matrix (GLCM) algorithms were employed in retrospective analysis of MR images of primary osteosarcoma localized in distal femur prior to the OsteoSa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 21 publications
1
27
1
Order By: Relevance
“…Finally, the results of the Kolmogorov-Smirnov test were used as criterion if data were normally distributed (Table 3). In previous publications it has been shown that some parameters of the image can describe similar [25] or complementary [17] properties. Therefore, we tested possible relationship between two parameters of monofractal (D bin and Λ) and textural (S IDM and S E ) analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the results of the Kolmogorov-Smirnov test were used as criterion if data were normally distributed (Table 3). In previous publications it has been shown that some parameters of the image can describe similar [25] or complementary [17] properties. Therefore, we tested possible relationship between two parameters of monofractal (D bin and Λ) and textural (S IDM and S E ) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The term N g is the number of gray levels in the image. Their mathematical definitions and detailed explanations can be found in [17]. The meaning of all parameters (fractal and textural) used in this investigation are summarized in Table 2.…”
Section: Quantification Of the Grayscale Imagementioning
confidence: 99%
“…Five GLCM features were calculated: angular second moment (ASM), inverse difference moment (IDM), contrast, correlation, and entropy using the GLCM Texture plugin for ImageJ v1.52u as previously explained in detail [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The GLCM calculates how often a pixel with gray-level (grayscale intensity) value i occurs either horizontally, vertically, or diagonally to adjacent pixels with the value j [39]. GLCM indices were computed using ImageJ 1.5.2 software (Nationa Institute of Health, Bethesda, MD, USA), by use of the GLCM TextureToo plugin [40,41].…”
Section: Glcm Analysismentioning
confidence: 99%